Linking phenylpropanoid metabolism, lignin deposition, and plant growth inhibition. (April 2019) - Muro-Villanueva, Fabiola; Mao, Xiangying; Chapple, Clint
Graphical abstract: Highlights: Reduction in lignin content often results in growth inhibition. Xylem-specific lignin complementation circumvents dwarfism. Alterations in gene regulation play a role in phenylpropanoid homeostasis and its impact on plant growth. The mechanisms that lead to dwarfism in low-lignin plants remain unknown. Abstract : Lignin, a polymer found in the plant secondary cell wall, is a major contributor to biomass' recalcitrance toward saccharification. Because of this negative impact toward the value of lignocellulosic crops, there is a special interest in modifying the content and composition of this important plant biopolymer. For many years this endeavor has been hindered by the plant growth inhibition that is often associated with manipulations to phenylpropanoid metabolism. Although the actual mechanism by which dwarfism arises remains unknown, recent advances in tissue-specific lignin complementation and better understanding of phenylpropanoid transcriptional regulation has made it possible to disentangle lignin modification from perturbations in plant development.